Hierarchical and heterogeneous multiphase metallic nanomaterials and laminates - Misra, Amit; Göken, Mathias; Mara, Nathan A.; Beyerlein, Irene J. (Mrs Bulletin, 2021)
The strength and plasticity of metallic composites is reviewed in terms of (1) hierarchical morphologies in metallic nanocomposites, such as Cu–Mo, Zr–Nb, Al–Si, and (2) heterogeneous interface behavior and compositionally graded interfaces in metallic laminates, such as Cu/bronze, Ti/Al, Fe/Cu, Cu/Nb. Hierarchical architectures of multiple phases with varying sizes and morphologies are particularly effective in enhancing yield strength, due to the strong glide dislocation interactions with their nanoscale features; plastic deformability, due to increased strain hardening from microstructure hierarchy. Enhanced toughening is attributed to impedance of crack growth via deflection along interfaces that have relatively low shear strength and bridging via relatively softer microscale composite domains. In laminates, the constraint from an interface affected zone arising from geometrically necessary dislocations can lead to enhanced strain hardening and plasticity.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Dislocations; Microstructure; Multiscale; Strength